Preparation method and application of graphene oxide silicon carbide nanowire composite aerogel
By using citric acid as a crosslinking agent under hydrothermal reaction conditions, graphene oxide and silicon carbide nanowires are crosslinked, which solves the problems of high reaction temperature and strict conditions in the prior art, and realizes the method of preparing graphene oxide silicon carbide nanowire composite aerogel at low temperature, which is suitable for large-scale production.
Patent Information
- Application Number
- CN202311209701.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-19
- Publication Date
- 2025-03-21
AI Technical Summary
In the prior art, when preparing graphene oxide silicon carbide nanowire composite aerogel, the reaction temperature is high and the reaction conditions are strict, making it difficult to achieve large-scale production.
Citric acid is used as the crosslinking agent, and under hydrothermal reaction conditions, graphene oxide is fully crosslinked with the surface-treated silicon carbide nanowires to form graphene oxide silicon carbide nanowire hydrogel, and aerogel is obtained by freeze-drying.
The preparation of graphene oxide silicon carbide nanowire composite aerogel at low temperature is realized, which simplifies the process, reduces energy consumption, and is suitable for large-scale production.
Smart Images

Figure CN119661186A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of graphene aerogels, and in particular to a method for preparing a graphene oxide silicon carbide nanowire composite aerogel. Background Art
[0002] Graphene is a new material in which carbon atoms connected by sp2 hybridization are tightly stacked into a single-layer two-dimensional honeycomb lattice structure. Graphene has excellent optical, electrical and mechanical properties, and has important application prospects in materials science, micro-nano processing, energy, biomedicine and drug delivery. It is considered to be a revolutionary material in the future. Graphene aerogels (GAs) inherit the excellent properties of graphene. They use the excellent properties of graphene from a macroscopic perspective to construct a graphene-based assembly structure material. Graphene aerogels themselves have all the physical properties of aerogels. They are porous materials with developed pores formed by stacking graphene sheets with graphene as the basic unit. Due to its special structure, its mechanical properties are poor. Therefore, it is composited with silicon carbide nanowires with high mechanical properties to prepare graphene oxide silicon carbide nanowire composite aerogels, thereby improving its mechanical properties.
[0003] At present, graphene oxide silicon carbide nanowire composite aerogel is mainly prepared by in-situ synthesis and chemical vapor deposition. In-situ synthesis is a new method for preparing composite materials that has been developed recently. The basic principle is that chemical reactions occur between different elements or compounds under certain conditions, and one or several ceramic phase particles are generated in the metal matrix to achieve the purpose of improving the performance of a single metal alloy. In the composite material prepared by this method, the reinforcement nucleates and grows spontaneously in the metal matrix. Therefore, the surface of the reinforcement is pollution-free, the matrix and the reinforcement have good compatibility, and the interface bonding strength is high. At the same time, unlike other composite materials, the cumbersome reinforcement pretreatment process is omitted, simplifying the preparation process. Although in-situ synthesis technology has many advantages such as low synthesis cost, fine and uniform distribution of product particles, no pollution on the surface of the reinforcement phase and good wettability with the matrix, high interface bonding strength, and the volume ratio of the reinforcement phase can be adjusted over a wide range, most of the in-situ synthesis processes and in-situ reaction systems are still in the test and development research stage, and there are still many problems, specifically: the in-situ synthesis system is limited, and sometimes the required structure cannot be generated by the reaction; the content and ratio of the reactants have a great influence on the generation and reaction rate of the reaction and are difficult to control; the density of the obtained product is not high; the reaction needs to be carried out at extremely high temperature, the process is cumbersome and requires special instruments and equipment, time-consuming and consumables, etc., making it difficult to achieve large-scale production and application.Yehong Cheng et al. prepared graphene oxide silicon carbide nanowire composite aerogel by chemical vapor deposition, and the reaction required a temperature of 1100°C (YHCheng, MYTan, P.Hu, XHZhang, BQSun, LWYan, SBZhou, WBHan, Strong and thermostable SiC nanowires / graphene aerogel with enhanced hydrophobicity and electromagnetic wave absorption property, Applied Surface Science, 448 (2018) 138-144); Jing-Peng Chen et al. prepared graphene oxide silicon carbide nanowire composite aerogel by in situ synthesis, and the reaction temperature needed to reach 1450°C, and the reaction conditions were strict (JPChen, H.Jia, Z.Liu, QQKong, ZHHou, LJXie, GHSun, SCZhang, CMChen, Construction of C-Siheterojunction interface in SiC whisker / reduced graphene oxide aerogels for improving microwave absorption,Carbon,164(2020)59-68).
[0004] Therefore, when currently using chemical vapor deposition and in-situ synthesis methods to prepare graphene oxide silicon carbide nanowire composite aerogels, the required reaction temperature is high and the reaction conditions are harsh. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a graphene oxide silicon carbide nanowire composite aerogel, using citric acid as a crosslinking agent, under hydrothermal reaction conditions, graphene oxide and surface-treated silicon carbide nanowires are fully crosslinked to obtain a graphene oxide silicon carbide nanowire hydrogel, and finally the obtained hydrogel is freeze-dried to form a graphene oxide silicon carbide nanowire aerogel. The method of the present invention is simple to operate, the reaction conditions are easy to control, and it is suitable for large-scale production, which solves the problems of high reaction temperature and harsh reaction conditions when preparing graphene oxide silicon carbide nanowire composite aerogel using chemical vapor deposition and in-situ synthesis methods.
[0006] In order to solve the above technical problems, the technical solution provided by the present invention is:
[0007] In a first aspect, the present invention provides a method for preparing a graphene oxide silicon carbide nanowire composite aerogel, comprising the following steps:
[0008] (1) dispersing graphene oxide in deionized water to prepare a graphene oxide aqueous solution;
[0009] (2) adding NaOH-treated silicon carbide nanowires to the graphene oxide aqueous solution of step (1), stirring thoroughly to obtain a graphene oxide silicon carbide nanowire mixed solution;
[0010] (3) adding citric acid to the graphene oxide silicon carbide nanowire mixed solution in step (2), stirring thoroughly to obtain a graphene oxide silicon carbide nanowire mixed reaction solution;
[0011] (4) subjecting the mixed reaction liquid of graphene oxide and silicon carbide nanowires in step (3) to a hydrothermal reaction to obtain a GO / SiC nanowire hydrogel;
[0012] (5) freeze-drying the GO / SiC nanowire hydrogel in step (4) to obtain GO / SiC nanowire aerogel.
[0013] Furthermore, the concentration of the graphene oxide aqueous solution described in step (1) is 2 mg / mL.
[0014] Furthermore, the NaOH solution in step (2) is 2 mol / L.
[0015] Furthermore, the stirring time in step (2) is 2-4 hours.
[0016] Furthermore, the ratio of the amount of citric acid added in step (3) to the amount of silicon carbide nanowire material is 1:1.
[0017] Furthermore, the hydrothermal reaction conditions in step (4) are 120°C
[0018] Furthermore, the hydrothermal reaction time in step (4) is 9-12 hours.
[0019] Furthermore, the freezing temperature in step (5) is -42°C
[0020] Furthermore, the freeze-drying time in step (5) is 24 hours.
[0021] In a second aspect, the present invention provides an application of the method for preparing graphene oxide silicon carbide nanowire composite aerogel in preparing graphene oxide silicon carbide nanowire composite aerogel.
[0022] Based on the above technical solutions, the technical effects that can be achieved by the present invention are:
[0023] 1) The preparation method is simple to operate, the reaction conditions are easy to control, the yield is as high as 80%, and graphene oxide silicon carbide nanowire composite aerogel with good performance can be prepared quickly and efficiently;
[0024] 2) The graphene oxide silicon carbide nanowire composite aerogel prepared by the present invention has good mechanical properties and is suitable for large-scale promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 This is the SEM image of the GO / SiC nanowire aerogel prepared in Example 1;
[0027] Figure 2 This is a macroscopic image of the GO / SiC nanowire aerogel prepared in Example 1;
[0028] Figure 3 This is the SEM image of the GO / SiC nanowire aerogel prepared in Example 2;
[0029] Figure 4 This is a macroscopic image of the GO / SiC nanowire aerogel prepared in Example 2;
[0030] Figure 5 This is the SEM image of the GO / SiC nanowire aerogel prepared in Example 3;
[0031] Figure 6 This is a macroscopic image of the GO / SiC nanowire aerogel prepared in Example 3;
[0032] Figure 7 This is the weighing mass diagram of GO / SiC nanowire aerogel prepared in Example 3;
[0033] Figure 8 This is a SEM image of the cross-linking of GO / SiC nanowire aerogel prepared in Example 3;
[0034] Fig. 9 Analysis diagram of mechanical properties of GO aerogel and GO / SiC nanowire aerogel as control examples. DETAILED DESCRIPTION
[0001] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the embodiments described are only part of the embodiments of the present invention, rather than all of the embodiments.
[0002] Therefore, the following detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present invention.
[0003] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.
[0004] The invention discloses a method for preparing a graphene oxide silicon carbide nanowire composite aerogel. The preparation of the graphene oxide silicon carbide nanowire composite aerogel comprises the following steps: (1) dispersing graphene oxide in deionized water to prepare a graphene oxide aqueous solution; (2) uniformly mixing the surface-treated silicon carbide nanowires with the graphene oxide aqueous solution obtained in step (1); (3) adding citric acid and cross-linking under hydrothermal conditions to form a hydrogel; and (4) freeze-drying the hydrogel obtained in step (3) to obtain a block aerogel product with a stable shape.
[0005] Example 1
[0006] (1) dispersing 40 mg of graphene oxide in deionized water to prepare a graphene oxide aqueous solution with a concentration of 2 mg / ml;
[0007] (2) adding 80 mg of silicon carbide nanowires treated with 2 mol / L NaOH to the graphene oxide aqueous solution of step (1), stirring thoroughly for 2-4 h to obtain a graphene oxide silicon carbide nanowire mixed solution;
[0008] (3) adding citric acid to the graphene oxide silicon carbide nanowire mixed solution in step (2), with the molar ratio of silicon carbide nanowire: citric acid = 1:1, and stirring thoroughly to obtain a graphene oxide silicon carbide nanowire mixed reaction solution;
[0009] (4) subjecting the mixed reaction solution of graphene oxide and silicon carbide nanowires in step (3) to a hydrothermal reaction at 120° C. for 9 h to obtain a GO / SiC nanowire hydrogel;
[0010] (5) Freeze-drying the GO / SiC nanowire hydrogel in step (4) at -42°C for 24 h to obtain GO / SiC nanowire aerogel.
[0011] Example 2
[0012] (1) dispersing 40 mg of graphene oxide in deionized water to prepare a graphene oxide aqueous solution with a concentration of 2 mg / ml;
[0013] (2) adding 80 mg of silicon carbide nanowires treated with 2 mol / L NaOH to the graphene oxide aqueous solution of step (1), stirring thoroughly for 2-4 h to obtain a graphene oxide silicon carbide nanowire mixed solution;
[0014] (3) adding citric acid to the graphene oxide silicon carbide nanowire mixed solution in step (2), with the molar ratio of silicon carbide nanowire: citric acid = 1:1, and stirring thoroughly to obtain a graphene oxide silicon carbide nanowire mixed reaction solution;
[0015] (4) subjecting the mixed reaction solution of graphene oxide and silicon carbide nanowires in step (3) to a hydrothermal reaction at 120° C. for 12 h to obtain a GO / SiC nanowire hydrogel;
[0016] (5) Freeze-drying the GO / SiC nanowire hydrogel in step (4) at -42°C for 24 h to obtain GO / SiC nanowire aerogel.
[0017] Example 3
[0018] (1) dispersing 40 mg of graphene oxide in deionized water to prepare a graphene oxide aqueous solution with a concentration of 2 mg / ml;
[0019] (2) adding 80 mg of silicon carbide nanowires treated with 2 mol / L NaOH to the graphene oxide aqueous solution of step (1), stirring thoroughly for 2-4 h to obtain a graphene oxide silicon carbide nanowire mixed solution;
[0020] (3) adding citric acid to the graphene oxide silicon carbide nanowire mixed solution in step (2), with the molar ratio of silicon carbide nanowire: citric acid = 1:1, and stirring thoroughly to obtain a graphene oxide silicon carbide nanowire mixed reaction solution;
[0021] (4) subjecting the mixed reaction solution of graphene oxide and silicon carbide nanowires in step (3) to a hydrothermal reaction at 120° C. for 15 h to obtain a GO / SiC nanowire hydrogel;
[0022] (5) freeze-drying the GO / SiC nanowire hydrogel in step (4) at -42°C for 24 hours to obtain GO / SiC nanowire aerogel;
[0023] (6) Weighing the GO / SiC nanowire aerogel in step (5), the weight of the GO / SiC nanowire aerogel is 95.6 mg;
[0024] (7) By comparing the total mass of GO / SiC nanowire aerogel in step 6 with the total mass of reactants (120 mg), it can be concluded that the aerogel yield is approximately 80%.
[0025] Comparison example
[0026] (1) dispersing 40 mg of graphene oxide in deionized water to prepare a graphene oxide aqueous solution with a concentration of 2 mol / L;
[0027] (2) subjecting the graphene oxide reaction solution in step (1) to a hydrothermal reaction at 120° C. for 9 h to obtain a GO hydrogel;
[0028] (3) Freeze-drying the GO hydrogel in step (4) at -42°C for 24 h to obtain GO nanowire aerogel.
[0029] (4) The GO aerogel obtained in step (3) and the GO / SiC nanowire aerogel obtained in Example 3 were subjected to compression performance tests. Fig. 9 As shown, the compression performance of GO is improved by 0.034MPa by adding SiC NWs. It can be seen that after adding silicon carbide nanowires, the mechanical properties of the product are significantly improved.
[0030] The preparation method provided by the present invention can prepare a composite aerogel product with rich porous structure, compact structure and high cross-linking degree. Figure 8 It can be seen that the composite aerogel product provided by the present invention has a high degree of crosslinking. At the same time, compared with the existing chemical vapor deposition method and in-situ synthesis method, the preparation process provided by the present invention is simple, the reaction process is easy to control, and the reaction temperature is much lower than the temperature required by the chemical vapor deposition method and the in-situ synthesis method, which is suitable for large-scale promotion, and solves the current problems of using chemical deposition method and in-situ synthesis method to prepare graphene and silicon carbide composite aerogel, such as complex process, uncontrollable reaction generation and reaction speed, high equipment cost and high energy consumption.
[0031] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing graphene oxide silicon carbide nanowire composite aerogel, characterized in that: The following steps are involved: (1) dispersing graphene oxide in deionized water to prepare a graphene oxide aqueous solution; (2) adding NaOH-treated silicon carbide nanowires to the graphene oxide aqueous solution of step (1), stirring thoroughly to obtain a graphene oxide silicon carbide nanowire mixed solution; (3) adding citric acid to the graphene oxide silicon carbide nanowire mixed solution in step (2), stirring thoroughly to obtain a graphene oxide silicon carbide nanowire mixed reaction solution; (4) subjecting the mixed reaction liquid of graphene oxide and silicon carbide nanowires in step (3) to a hydrothermal reaction to obtain a GO / SiC nanowire hydrogel; (5) freeze-drying the GO / SiC nanowire hydrogel in step (4) to obtain GO / SiC nanowire aerogel.
2. The method for preparing the graphene oxide silicon carbide nanowire composite aerogel according to claim 1, characterized in that: The concentration of the graphene oxide aqueous solution described in step (1) is 2 mg / mL.
3. The method for preparing the graphene oxide silicon carbide nanowire composite aerogel according to claim 1, characterized in that: The NaOH solution in step (2) is 2 mol / L.
4. The method for preparing the graphene oxide silicon carbide nanowire composite aerogel according to claim 1, characterized in that: The stirring time in step (2) is 2-4h.
5. The method for preparing the graphene oxide silicon carbide nanowire composite aerogel according to claim 1, characterized in that: The ratio of the amount of citric acid added in step (3) to the amount of silicon carbide nanowire material is 1:
1.
6. The method for preparing the graphene oxide silicon carbide nanowire composite aerogel according to claim 1, characterized in that: The hydrothermal reaction condition in step (4) is 120°C.
7. The method for preparing the graphene oxide silicon carbide nanowire composite aerogel according to claim 1, characterized in that: The hydrothermal reaction time in step (4) is 9-12 hours.
8. The method for preparing graphene oxide silicon carbide nanowire composite aerogel according to claim 1, characterized in that: The freezing temperature in step (5) is -42°C.
9. The method for preparing the graphene oxide silicon carbide nanowire composite aerogel according to claim 1, characterized in that: The freeze-drying time in step (5) is 24 hours.
10. Use of the method for preparing graphene oxide silicon carbide nanowire composite aerogel according to any one of claims 1 to 9 in preparing graphene oxide silicon carbide nanowire composite aerogel.